Sustained COVID-19 community transmission and potential super spreading events at neglected afro-ecuadorian communities assessed by massive RT-qPCR and serological testing of community dwelling population - Vallejo-Janeta, Alexander Paolo; Morales-Jadan, Diana; Paredes-Espinosa, Maria Belen; Coronel, Barbara; Galvis, Heberson; Bone-Guano, Hugo Renato; Amador Rodriguez, Belen; Gomez Abeledo, Guadalupe; Freire-Paspuel, Byron; Ortiz-Prado, Esteban; Rivera-Olivero, Ismar; Henriquez-Trujillo, Aquiles Rodrigo; et al. (Frontiers in Medicine, 2022)
Background. Neglected ethnic minorities from underserved rural populations in Latin America are highly vulnerable to COVID-19 due to a poor health infrastructure and limited access to SARS-CoV-2 diagnosis. Esmeraldas is a mainly rural province of the Coastal Region of Ecuador characterized by a high presence of Afro-Ecuadorian population living under poverty conditions. Objective. We herein present a retrospective analysis of the surveillance SARS-CoV-2 testing in community dwelling population from Esmeraldas carried out by our university laboratory in collaboration with regional health authorities during the first week of October 2020, in a region where no public SARS-CoV-2 detection laboratory was available at that time. Results. A total number of 1,259 people were tested for SARS-CoV-2 by RT-qPCR, resulting in an overall infection rate of 7.7% for SARS-CoV-2, up to 12.1% in some communities. Interestingly, community dwelling super spreaders with viral loads over 108 copies/mL represented 6.2% of the SARS-CoV-2 infected population. Furthermore, anti-SARS-CoV-2 IgG serological tests were applied to the same study group, yielding an overall seroprevalence of 11.7% but as high as 24,47% at some communities. Conclusion. These results support recent and active COVID-19 community transmission in Esmeraldas province during the first semester of COVID-19 pandemic as it has been shown for other rural communities in the Ecuadorian Coastal Region.